2020
DOI: 10.1002/mp.14399
|View full text |Cite
|
Sign up to set email alerts
|

Statistical process control and process capability analysis for non‐normal volumetric modulated arc therapy patient‐specific quality assurance processes

Abstract: Applying statistical process control (SPC) to intensity-modulated radiotherapy (IMRT)/ volumetric modulated arc therapy (VMAT) patient-specific quality assurance (PSQA) program was recommended by the American Association of Physics in Medicine Task Group 218 report, but a comprehensive analysis of PSQA processes with non-normal distributions is lacking. This study investigates SPC and process capability analysis (PCA) methods for non-normal IMRT/VMAT PSQA processes. Methods: 1119 VMAT PSQAs were performed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 36 publications
2
32
0
1
Order By: Relevance
“…Previous studies have also found that PSQA processes are not normally distributed. 3,7,16,17,24,25 It was further found that, for a given linac, the optimal distribution models of GPRs varied by treatment site and gamma analysis criterion. There were also some inter-linac differences in the distributions of GPRs at the same treatment sites.…”
Section: F I G U R Ementioning
confidence: 98%
“…Previous studies have also found that PSQA processes are not normally distributed. 3,7,16,17,24,25 It was further found that, for a given linac, the optimal distribution models of GPRs varied by treatment site and gamma analysis criterion. There were also some inter-linac differences in the distributions of GPRs at the same treatment sites.…”
Section: F I G U R Ementioning
confidence: 98%
“…(). One of the most commonly used methods to empirically and automatically identify an appropriate transformation to apply on a skewed variable is the Box‐Cox transformation 7 . The Box‐Cox transformation for a positive response variable indexed by an unknown parameter λ is given asyλ=yλ1λ,ifλ0logy,ifλ=0,where the optimal value of λ is computed by the maximum likelihood estimation.…”
Section: Methodsmentioning
confidence: 99%
“…5 In the clinic, quality control tools have been recommended for intensity-modulated radiation therapy (IMRT) quality assurance (QA) by the American Association of Physicists in Medicine Task Group 218. 6,7 However, quality control for plan evaluation has been restricted by the limited availability of tools capable of analyzing patient data and efficiently producing visualizations from a large batch of patient files. The most recent and commonly used state-of-the-art method that utilizes anatomical data from existing patients to estimate plan quality and makes planning decisions is referred to as knowledge-based planning (KBP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top three subspecialties are radiation imaging (218 papers), radiation therapy (70 papers), and magnetic resonance (42 papers). Within the subspecialty of radiation therapy, the number of publications are 15 papers in the field of clinical implementation [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], 11 papers in the field of plan optimization [56][57][58][59][60][61][62][63][64][65][66], 14 papers in the field of plan evaluation [67][68][69][70][71][72][73][74][75][76][77][78][79][80], and 12 papers in the field of quality assurance [81][82][83][84][85][86][87][88]…”
Section: Scientific Researchmentioning
confidence: 99%